ASSESSMENT OF ADAPTATION AND SPARE CAPACITY IN CHILDREN WITH PATHOLOGY OF RESPIRATORY AGAINST SUBCLINICAL HYPOTHYROIDISM - Павликівська, Б. М.; Юрцева, А. П.; Боднар, О. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The purpose of the work. Study features of adaptive-reserve capacity in children of school age with acute and recurrent respiratory pathology on the background of subclinical hypothyroidism. Material and methods of investigation. The study involved 78 children schoolchildren aged 10 to 15 years. The study of the functional state of the pituitary-thyroid system by determining the level of thyroid stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3), the index of T3 / T4 is carried out. For comparative assessment of adaptation and reserve capacity in children two groups are formed. The main group included 33 children who where diagnosed subclinical hypothyroidism, comparison group consisted of 45 children with no clinical and laboratory signs of hypothyroidism. Сontrol group included 20 healthy children of the same age. A study of the functional state of the cardiovascular system using computer 12-lead ECG and ultrasound scanning in one - and two-dimensional mode. To diagnose adaptation-reserve determination and reserve-functionality child's body was calculated integral indices: the index of functional changes (IFC) and Robinson index (RI) according to special formulas. The results of the work. The most common disorders in children with respiratory disturbance of repolarization were observed, signs of myocardial hypoxia, sinus tachy- or bradycardia, QT prolongation and migration pacemaker. In surveyed children there were determined three types of hemodynamics: eukinetyc, hypokinetic and hyperkinetic. In children against subclinical hypothyroidism prevails hypokinetic type. The study showed that the satisfactory functioning of the circulatory system in children with disorders of the respiratory observed extremely rare. Found that poor adaptation and failure of adaptation are more common in patients children against subclinical hypothyroidism and type hypodynamic hemodynamics. Conclusions. 1. In school-age children with acute and recurrent respiratory disorders with clinical signs of subclinical hypothyroidism should be determined pituitary-thyroid status and metrics of the cardiovascular system. 2. To prevent the disruption of poor adaptation and adaptive-organism reserve capacity in children with respiratory disorders against the background of subclinical hypothyroidism should define the functional code changes and Robinson index. 3. In case of adaptation and reduction of reserve capacity of the organism in children with respiratory disorders against the background of hypothyroidism should be given a set of measures aimed at improving them. This will serve as basis for relapse prevention of respiratory diseases and improving the treatment of subclinical hypothyroidism.